Hubungan lingkar leher dan skor gaya hidup dengan tekanan darah sistolik pada guru SMP Negeri di Kabupaten Bojonegoro - Adhiestya Mayangsarie; Selfi Handayani; Anik Lestari (Poltekkes Kemenkes Aceh, 2026)
Background: In Indonesia, civil servants have the highest prevalence of hypertension (36.9%), with teachers included as a high-risk population. High blood pressure is influenced by anthropometric factors, including neck circumference as an indicator of upper body adiposity, as well as lifestyle factors affecting systolic blood pressure. However, studies examining these factors among teachers are scarce.Objective: This study aimed to investigate the relationship between neck circumference, lifestyle score, and systolic blood pressure in junior high school teachers in Bojonegoro Regency.Methods: An analytical observational study with a cross-sectional design was conducted. Eight public junior high schools were selected using cluster random sampling, followed by convenience sampling of 320 teachers from these schools. Neck circumference was measured using a tape with 0.1 cm accuracy, lifestyle score was assessed via a questionnaire, and systolic blood pressure was measured using a digital sphygmomanometer. Data were analyzed using multiple linear regression without adjusting for confounding variables.Results: Neck circumference was positively and significantly associated with systolic blood pressure (p < 0.001), whereas lifestyle showed no significant association (p = 0.402). The model explained 22.8% of the variability in the systolic blood pressure (R² = 0.228). The mean systolic blood pressure was 131.80 ± 18.71 mmHg.Conclusion: Neck circumference was significantly associated with systolic blood pressure, whereas lifestyle factors did not have a direct effect.